(3OQGSI eMGSHjI dLOhi GdeTQhYGJ (B((3c(B21) /s - (3YjO Mfaj, Rcjs; (3MGeO, eUWai UGOb s ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s, 1998)
(3GdfTGW GdGSJKeGQj h GdfTGW GdLGQj, eQGMd GfTGA GdeTQhY GdGSJKeGQj, JHhjH GdeTQhYGJ GdGSJKeGQjI hCgejI GdOQGSI, CgejI GSJNOGe GdJMdjd Gdcej aj GdJNWjW hGdQbGHI Ydi GdeTQhYGfJ GdGSJKeGQjI, GdGLgRI GdeTQaI Ydi Jbhje GdeTQhYGJ GdGSJKeGQjIs
(3edGMb U(B.299s
Keywords: (3GdGSJKeGQs; (3GdeTQhYGJ(B- (3ESJKeGQs